Modelling of single and binary adsorptions of heavy metals onto activated carbon - equilibrium studies - Abdullah, Luqman Chuah; Muhammad,; Jamari, Saidatul Shima; Choong, Thomas Shean Yaw (Universiti Putra Malaysia Press, 2010)
A series of batch laboratory studies were conducted to investigate the suitability of activated carbon SA2 for the removal of cadmium ions and zinc ions from their aqueous solutions. The single component equilibrium data were analyzed using the Langmuir and Freundlich isotherms. Overall, the Langmuir isotherm showed a better fitting for all adsorptions under investigation in terms of correlation coefficient and error analysis (SSE only 18.2 for Cd2+ and 47.95 for Zn2+). As the binary adsorption is competitive, extended Langmuir models could not predict the binary component isotherm well. The modified extended Langmuir models were used to fit the binary system equilibrium data. The binary isotherm data could be described reasonably well by the modified extended Langmuir model, as indicated in the error analysis.